2019
DOI: 10.1089/acm.2019.0062
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Medicine Provision in an Academic Hospital: Evaluation and Structuring Project

Abstract: Objectives: Complementary medicine (CM) has become increasingly available in hospital settings in several countries. Nonetheless, there are disparities in the provision and organization of CM between hospitals and even within a single hospital. This was the case at Lausanne University Hospital, where neither a registry of CM practices nor homogeneous guidelines for the provision of CM existed. The board of directors mandated the use of an internal consultant to assess practices, delineate the ward's needs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…We give information in the form of leaflets Efforts to increase demand for services such as promoting services to the public and health workers, were needed to increase public demand for complementary services. 9, 19 Our survey results showed that more than 50% were willing to have pranic therapy, and 77.5% were willing to recommend it to other people (Table 4). The main reason for receiving pranic service was disease severity (71%).…”
Section: "The Promotion Was Performed At the Opening It Is Also Promo...mentioning
confidence: 84%
“…We give information in the form of leaflets Efforts to increase demand for services such as promoting services to the public and health workers, were needed to increase public demand for complementary services. 9, 19 Our survey results showed that more than 50% were willing to have pranic therapy, and 77.5% were willing to recommend it to other people (Table 4). The main reason for receiving pranic service was disease severity (71%).…”
Section: "The Promotion Was Performed At the Opening It Is Also Promo...mentioning
confidence: 84%
“…Complementary and integrative medicine has been successfully integrated in academic centres and also appears to be of greater utility among patients with serious, chronic, or recurrent illnesses [6]. The first academic centre of its kind in Romandie, the Lausanne University Hospital (CHUV), began its clinical activity in the field after a pilot project in the oncology department supported by philanthropic foundations between 2017 and 2019 [7]. Today, the CHUV's Centre for Integrative and Complementary Medicine (CEMIC) delivers structured, specialised inpatient care to about 500 patients annually.…”
Section: A New Medical Servicementioning
confidence: 99%
“…Rodondi et al [7] reported that barriers to implementing complementary medicine are mainly due to the reimbursement strategy. The SwissDRG algorithm's classification method is accurate when patients are admitted specifically for complementary and integrative medicine management, such as in a rehabilitation clinic.…”
Section: Barriers For Developmentmentioning
confidence: 99%
See 1 more Smart Citation